Successful strategies for multinational companies in China - Chen, Ting (My University, 2011)
As one of the largest emerging markets, China's enormous population and economic boom have recently attracted many multinational companies (MNCs). In the past two decades, the Chinese government has reformed the economy, installed market forces, and opened various industries to foreign investors. With the admission of China to the World Trade Organisation (WTO) in 2001, it signalled the growing maturity of the Chinese market and its expectation for further increase of investment opportunities. Successful MNCs have regarded investing in China as a long-term strategic approach in which they have tried to reach a balance between global orientation and local conditions so that they could maximise market coverage, minimise risk exposure, and optimise their overall performance for sustainable prosperity. The research was qualitative in nature, conducted in the interpretive paradigm, using in-depth, semi-structured interviews with three successful MNCs presently operating in China. In this paper, the author discusses the conceptual background for China's business environment, problems faced by the executives of MNCs and classical strategy theories. as well as the country specific strategies related to China. The results of this study are presented through a discussion of the research findings from the interviews in relation to the propositions, and provide useful guidelines for MNCs investing or intending to invest in the Chinese economy. The research identified the following successful strategies for MNCs investing in China: the appropriate market entry mode, adaptation to local environment, developing guanxi to build trust and credibility, cross-cultural management in HR, creating good Chinese brand names, efficient brand communication and emotional marketing, chief executive's long-term commitment to the Chinese market, and establishing a "China Centre" as well as diversified corporate approaches to the indigenous market.
MBA - WBS
Keywords: Strategic planning; Multinational companies; China